Android security reinforcing scheme of intelligent terminal based on certificate chain authentication mechanism - Jiaren JIANG; GLiu JIAN; Weiqing WANG (Dianxin kexue)
With the prosperous development of information technologies and mobile internet popularity of information-based on a global basis,it is necessary to analyze and research the security problems for Android,which is one of the most important technologies in the emerging field of mobile internet and intelligent terminals.The certificate chain authentication mechanism played a critical role as protecting the core of the terminals against some intrusion attacks in the security phases.